Hypoxia inducible factor-1 alpha (Hif-1 alpha) polymorphism in lymphoma and reactive lymphoid hyperplasia - YILMAZ, SEMA; Yoruk, Asim; Zemheri, Itır Ebru; Kuskucu, Aysegul; Suakar, Oznur; Imamova, Nergiz; Canizci, Pinar (Asian Pacific Journal of Cancer Biology, 2019)
Background: Lymphadenopathy is an abnormality in the size or the character of the lymph node. It may be a manifestation of infectious and malignant diseases. Reactive lymphoid hyperplasia is a benign form of lymphadenopathy. Cells develop numerous adaptive responses regulated by hypoxia inducible factor-1 alpha (Hif-1 alpha) against hypoxic stress. Purpose: Hif-1alpha may play a role in the process of carcinogenesis in the early stage of cancer. We aimed to investigate the most common polymorphism of Hif-1α C1772T and G1790A gene polymorphisms in reactive lymphoid hyperplasia and lymphoma cases. Methods: Eighty-six paraffin-embedded blocs [51 (59,3%) reactive lymphoid hyperplasia; (40,7%) lymphoma] were examined. DNA was extracted from these samples and the polymerase chain reaction (PCR) was carried out. After DNA isolation, Hif-1α C1772T and G1790A polymorphisms were investigated with pyrosequencing. Results: Cases were (29,1%) girls and 61 (70,9%) boys. The mean age was 91,47±57,96 and 142,46±41,66 for reactive lymphoid hyperplasia and lymphoma group, respectively. There was no Hif-1α C1772T gene polymorphism in both group, but Hif-1α G1790A gene polymorphism was recorded in 14 cases (reactive lymphoid hyperplasia 10, lymphoma 4). Although Hif-1α G1790A gene polymorphism was seen a little higher in reactive lymphoid hyperplasia cases than that of lymphoma, no meaningful relationship was found statistically between two groups (p>0,05). Conclusion: Hif-1α C1772T and G1790A gene polymorphisms had been interrogated in cancer etiology and emphasized in some cancers. In our study, considering of a few of Hif-1α G1790A gene polymorphism in reactive lymphoid hyperplasia group, it should be investigated with large studies in terms of understanding of the behavior of Hif- 1α gene polymorphisms in children with lymphadenopathy.